Comparative Evaluation and Measure of Accuracy of ELISAs, CLIAs, and ECLIAs for the Detection of HIV Infection among Blood Donors in China. (14th August 2020) - Chang, Le; Zhao, Junpeng; Guo, Fei; Ji, Huimin; Zhang, Lu; Jiang, Xinyi; Wang, Lunan
Abstract : Background . Enzyme-linked immunosorbent assay (ELISA) is the only serological method approved for blood screening in China. Automated chemiluminescence immunoassay (CLIA) and electrochemiluminescence immunoassay (ECLIA) had been used in clinical laboratories but not applied to screen HIV among blood donors. This study aimed to evaluate the performance of ELISA, CLIA, and ECLIA, focusing on the feasibility of CLIA/ECLIA for blood screening. Method . 1029 blood donations from 14 blood centers screened by ELISA were enrolled in the study. All plasma samples were tested by eight ELISA assays in 16 blood centers, followed by the detection of CLIA and ECLIA methods in the National Center for Clinical Laboratories (NCCL), further confirmed by nucleic acid testing (NAT) and Western blot (WB). Results . Of 1029 samples, 136 were confirmed as HIV positive. CLIA and ECLIA assay had similar sensitivities with ELISAs but showed higher specificity (CLIA: 99.1%, 885/893; ECLIA: 99.0%, 884/893), concordance rate (CLIA: 99.2%, 1021/1029; ECLIA: 99.1%, 1020/1029), and positive predictive value (PPV) (CLIA: 94.4%, 136/144; ECLIA: 93.8%, 136/145) than most of ELISA kits (>5 ELISAs) (P < 0.05 ). Kappa values of CLIA (0.967) and ECLIA (0.963) were the highest among all the serologic assays. Among 451 samples with initial ELISA reactivity, 315 were negatives, of which 307 (97.5%) and 306 (97.1%) were detected as nonreactive by CLIA (8 nonspecific reactions) and ECLIA (9 nonspecific reactions), respectively. Conclusion . Compared with ELISA, CLIA and ECLIA are more specific and accurate in detecting HIV antibody/antigen and can keep more nonspecifically reactive donors detected by ELISA. CLIA and ECLIA can be used for the improvement of serological blood screening strategy to avoid the unnecessary loss of blood donors.